The Heritage and its surroundings in the face of damage - Mohamad Naal (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Heritage is the rest of the past nations, the Inspirational of the present nations, and the embodiment of their values, and due to the importance of the architectural heritage in human civilizations, and due to the increasing risks that encroach on this heritage and distort its value, this study deals with the impact of these distortions, whether on the heritage building or its surroundings, indicating the importance of preserving the architectural heritage from the damages facing it, whether it is natural or manmade, by reviewing many examples of damages and infringements, discussing the weakness of regulations and procedures to preserve this heritage.